Boosting the safety and energy density of molybdenum disulfide/carbon nanotubes based solid-state sodium-ion supercapacitors with an ionogel electrolyte. (December 2020) - Xing, C.X.; Zhang, H.T.; Pan, S.S.; Yao, M.; Li, B.S.; Zhang, Y.Q.; Zhang, S.J.
Abstract: Solid-state energy storage devices exhibit superior safety and energy density. However, their practical applications are still limited by the lower conductivity and ion transfer rate. The performances of sodium ion capacitors (SICs) are determined by the combination of device configuration, electrodes, and electrolyte. Therefore, the configuration optimization of solid-state SICs (SS-SICs) is critically important. Here, the fabrication of a safer high-energy-density SS-SIC is demonstrated by using flake-shaped molybdenum disulfide/carbon nanotube nanohybrids and sodium-ion ionogel electrolytes. The microstructures of nanohybrids could support shortened migration paths for sodium ions and can buffer the volume change of electrochemical reactions. Moreover, the optimized sodium-ion ionogel electrolyte was found to exhibit improved flame-retardant ability, accelerated ionic conductivity, and excellent sodium migration rate. Electrochemical analysis and molecular simulation methods of energy storage behaviors were used to uncover the origin of improved performances at higher temperatures. The optimized SS-SIC could deliver a high energy density up to 115.7 W h kg −1  at 70 °C and excellent durability with 81% retention after 8000 cycles. Therefore, a new energy supply device is provided for equipment operating at higher temperatures. Graphical abstract: The solid-state sodium-ion supercapacitor was assembled with the molybdenum disulfide/carbon nanotube electrode anode, the activated carbon electrode cathode, and the ionogel electrolyte. Electrochemical analysis of energy storage behaviors and molecular simulation methods were used to uncover the origin of improved performances at higher temperatures. Image 1 Highlights: Construction a high capacity MoS2 /CNT nanohybrid electrode materials through a simple hydrothermal route. Synthesis of a 3.8 V sodium-ion ionogel electrolyte with modulated ion transport mobility. A solid-state sodium-ion capacitor exhibits enhanced electrochemical performances at high temperatures.